Parents' attitude towards inclusive program in sports schools - Salapura Simo (University Educons, Faculty of Sports and Tourism, Novi Sad, 2013)
This paper researches the attitude of the parents whose children are not disabled towards the inclusive program that is being implemented in sport schools. The aim of the research was to determine the parent's social distance in relation to the inclusive program, the children who have developmental disabilities, as well as their willingness to continue to participate in inclusive programs conducted in sports schools. The research was conducted during the period from 1st February to 1st March 2013 in the 'Zrenjanin' Karate club. It included 58 parents of non-disabled child athletes, members of the 'Zrenjanin' Karate club, already taking part in the inclusion program. The research conclusions indicate that most parents have a positive attitude towards the inclusive program, as well as towards people with developmental disabilities. It can also be concluded that the parents have a high level of readiness to help inclusive practice at the club. Also, most parents have a positive attitude towards inclusive camps. Very few parents think that it is not necessary to include defectologists in the inclusive program.